Provably secure secret sharing scheme based on bilinear maps - LI Hui-xian1; PANG Liao-jun2 (Tongxin xuebao)
A method to construct provable secure secret sharing scheme using bilinear pairing was recommended.Firstly,the semantic security definition for secret sharing scheme is given,which is developed from the standard definition of semantic security for the public key cryptosystems.Then,a new secret sharing scheme based on the bilinear maps is pro-posed,with its correctness,security and performance analyzed and proven subsequently.Compared with the existing schemes,the proposed scheme is provably secure.At the same time,the proposed scheme departs the private key compu-tation of participants from the secret distribution process and the dealer does not have to securely save each participant’s private key,which makes this scheme more secure and more efficient.Therefore,the proposed scheme is more applicable than the existing ones.